Spatiotemporal transformations of the Laguna de Sonso Nature Reserve (Colombia) mid-twentieth century to the early-twenty first century - Oscar Buitrago Bermúdez; Marco Antonio Aguirre (Anales de Geografía de la Universidad Complutense, 2017)
The current capitalist economic model is increasingly taking hold of natural resources at the global level, including soil, forests and water. In this context, during the last seventy years, the economic elites backed by development policies, have promoted the expansion of the sugar cane monoculture in the department of Valle del Cauca and other regions of Colombia. Thus, wetlands—strategic ecosystems due to the richness of their fauna and flora, landscape beauty, and capacity to serve as a source of livelihood for local communities—are threatened for the expansion of the crop. To understand this process, firstly, we performed a multi-temporal analysis of the land covers which comprise the complex wetland system of the Laguna de Sonso Nature Reserve (from mid-twentieth century to the early twentyfirst century). And, secondly, we incorporated qualitative research techniques. Results allow local knowledge to advance for the protection and conservation of wetlands, as well as in their planning and management.